Efektivitas Antibakteri Ekstrak Etanol Kulit Umbi Ubi Jalar Ungu (Ipomoea batatas L) terhadap Staphylococcus aureus dan Salmonella typhi. - Dewi Isnaeni; B, Suherman (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Research about antibacterial effectiveness of ethanol extract of purple sweet potato tuber skin (Ipomoea batatas L.) against Staphylococcus aureus and Salmonella typhi has been conducted. This study aims to determine the antibacterial effectiveness of ethanol extract of Purple Sweet Potato Tuber Skin against the growth of Staphylococcus Aureus and Salmonella Typhi and the most effective concentration. This research is expected to provide additional information about alternative medicine that has proven effective in laboratory testing for the community as an antibacterial agent. This type of research uses the agar diffusion method, Staphylococcus Aureus, namely with an average zone of resistance for concentrations of 2% w/v, 4% w/v, 6% w/v and 8% w/V of 12 mm, 16.26 mm, 24.26 mm, 27.1 mm and for positive control 31.16 mm, negative control around 6 mm. For the growth of Salmonella typhi, namely with an average zone of inhibition for concentrations of 2% w/v, 4% w/v, 6% w/v and 8% w/V of 12.83 mm, 17 mm, 25 mm, 26, 6 mm and for positive controls 32.5 mm, negative controls around 6 mm. Statistical tests using SPSS 24 (Statistical Product and Service Solutions) based on Analysis of Variance (ANAVA) showed that there were significant differences between each treatment and the positive control. Conclusion Purple Sweet Potato Tuber Skin is effective as an antibacterial.